Effect of Bad Habits on the Growth of School Students: A Cross-Sectional Study: Pengaruh Kebiasaan Buruk terhadap Pertumbuhan Siswa Sekolah: Sebuah Studi Cross-Sectional - Jassim, Firas A.; Tiryag, Ali Malik; Issa, Sajjad Salim (Indonesian Journal on Health Science and Medicine, 2024)
Background: Lifestyle is the primary element influencing health, according to the health field theory. Objectives: To identify the effect of bad habits on school students' growth. Methods: A collection of elementary and middle schools in Basrah served as the study's site. For the study, an adequate sample of 300 male and female students was selected, with 133 male and female students and 167 female students participating. A survey with closed-ended questions was used to collect data. The questionnaire is divided into two pieces. The first focuses on the social and demographic traits of pupils, such as their age, gender, study style, height, weight, and parent's occupation. Results: The majority of the pupils were between the ages of nine and twelve. Women participated at a higher rate than men did. Since the majority of the students' fathers worked and their mothers were housewives, the majority of the participants were middle schoolers. Every student provided a written response to the questions. Conclusion: Bad behaviors and the parents' occupations were significantly correlated, and the students' stage and registration were related Highlights: Lifestyle significantly influences health, per health field theory. Examine bad habits' impact on students' growth. Bad habits correlate with parents' occupations and students' school stages. Keywords: Effect, Bad Habits, Growth, School Students